1984
DOI: 10.1002/fld.1650040704
|View full text |Cite
|
Sign up to set email alerts
|

A single cell high order scheme for the convection‐diffusion equation with variable coefficients

Abstract: SUMMARYA new finite differenoe scheme for the convection-diffusion equation with variable coefficients is proposed. The difference scheme is defined on a single square cell of size 2h over a 9-point stencil and has a truncation error of order h4. The resulting system of equations can be solved by iterative methods. Numerical results of some test problems are given.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
179
0
1

Year Published

1996
1996
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 227 publications
(181 citation statements)
references
References 4 publications
1
179
0
1
Order By: Relevance
“…Dennis and Hudson [1], MacKinnon and Johnson [2], Gupta et al [3], Spotz and Carey [4] and Li et al [5] have demonstrated the efficiency of the high order compact schemes on the streamfunction and vorticity formulation of 2-D steady incompressible Navier-Stokes equations.…”
Section: Introductionmentioning
confidence: 99%
“…Dennis and Hudson [1], MacKinnon and Johnson [2], Gupta et al [3], Spotz and Carey [4] and Li et al [5] have demonstrated the efficiency of the high order compact schemes on the streamfunction and vorticity formulation of 2-D steady incompressible Navier-Stokes equations.…”
Section: Introductionmentioning
confidence: 99%
“…The derivation of fourth-order finite difference approximations on the rotated grid is based on Taylor series expansions which is similar to the one investigated by Gupta, Manohar and Stephenson [7,12]. To formulate the rotated fourth-order nine-point finite difference scheme, we consider the following grid stencil: By considering all alternate points on the solution domain for the case 9 n as illustrated in FIGURE 2, a point iterative scheme based on the rotated finite difference formula can be formulated.…”
Section: The Npf Finite Difference Schemesmentioning
confidence: 99%
“…A set of such boundary approximations are listed in [14]. On the contrary, the compact scheme does not need any special boundary approximation [7].…”
Section: The Npf Finite Difference Schemesmentioning
confidence: 99%
See 1 more Smart Citation
“…See [45,33] for a review on fundamental formulations of incompressible Navier-Stokes equations. The appearance and growing popularity of "compact schemes" brought a renewed interest in the aforementioned methods ( [26,17,18,43,42,19,50,35,1,13]). The purestreamfunction formulation for the time-dependent Navier-Stokes system in planar domains has been used in [31,32,30] some twenty years ago.…”
Section: Introductionmentioning
confidence: 99%